EVALUATION OF THE EPIDEMIOLOGICAL IMPACT OF VACCINATION AGAINST SARS-COV-2 IN THE STATE OF GOIÁS IN 2021 (Interdisciplinary Studies Journal, 2025)
ABSTRACT:Introduction: Vaccines against the COVID-19 pandemic were an efficient strategy in reducing the number of cases of infection by the SARS-COV2 virus and its variants. Objective: To evaluate the impact of the vaccination campaign against COVID-19, in the state of Goiás. Methodology: Cross-sectional, retrospective epidemiological study in which the influence of the total number of doses of vaccines against COVID-19 applied on the number of confirmed cases, the number of confirmed cases that required ICU admission, the average length of stay in the ICU and the clinical outcome of these cases admitted to the ICU. Results: During the period analyzed, 10,813,451 doses of vaccine were administered and 634,336 new cases were confirmed. In epidemiological week 9, the highest value of the analyzed period was recorded, while after epidemiological week 28, there was a slowdown in the number of new confirmed cases. In 2021, an increase in the number of hospitalizations was observed in the first half of the year. From epidemiological week 29 onwards, there was a decrease in the number of new ICU admissions. The average length of stay in the ICU was 10.9 days and on average 47.9% of confirmed cases of COVID-19 admitted to the ICU were discharged from the hospital. Conclusion: Advances in vaccination in the state of Goiás generated a progressive reduction in the number of confirmed cases and confirmed cases that required ICU admission. For the length of stay in the ICU of confirmed cases of COVID-19 and respective clinical outcome, this relationship was not observed.Keywords: COVID-19; Vaccination; SARS-COV-2; Goiás.
Keywords: COVID-19; SARS-CoV-2; Goiás; Vaccination